2018
DOI: 10.3892/ol.2018.9173
|View full text |Cite|
|
Sign up to set email alerts
|

Study of miR-143 expression in stomach cancer

Abstract: The present study was planned to investigate miR-143 expression during stomach cancer. The study explored the relationship between miR-143 expression and clinicopathological characteristics including proliferation, migration and apoptosis of stomach cancer cells. Sixty-three samples from each of stomach cancer tissue and surrounding tissue were obtained. Total RNA was extracted. The expression levels of miR-143 from stomach cancer tissue as well as from surrounding tissue were measured by semi-quantitative PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Moreover, it has been shown that miR-30a-3p can exert anti-cancer effects by targeting on both COX-2 and BCL9, which significantly affects the development of gastric cancer induced by Helicobacter pylori, providing new insights to better understand the mechanism underlying the disease development 45. Similarly, miR-944,46 miR-139,47 miR-511b48 and miR-143-3p49,50 have also been shown to be the inhibiting factors of the malignant behavior of gastric cancer. It has been also shown that MAD2L1 exerts function as a cancer-promoting factor in the gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that miR-30a-3p can exert anti-cancer effects by targeting on both COX-2 and BCL9, which significantly affects the development of gastric cancer induced by Helicobacter pylori, providing new insights to better understand the mechanism underlying the disease development 45. Similarly, miR-944,46 miR-139,47 miR-511b48 and miR-143-3p49,50 have also been shown to be the inhibiting factors of the malignant behavior of gastric cancer. It has been also shown that MAD2L1 exerts function as a cancer-promoting factor in the gastric cancer.…”
Section: Discussionmentioning
confidence: 99%